2014
DOI: 10.1088/1367-2630/16/6/063049
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal conductance distribution of Kitaev edge modes in topological superconductors

Abstract: A two-dimensional superconductor with spin-triplet p-wave pairing supports chiral or helical Majorana edge modes with a quantized (length L-independent) thermal conductance. Sufficiently strong anisotropy removes both chirality and helicity, doubling the conductance in the clean system and imposing a super-Ohmic L 1/ decay in the presence of disorder. We explain the absence of localization in the framework of the Kitaev Hamiltonian, contrasting the edge modes of the two-dimensional system with the one-dimensio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…The presence of this term is what distinguishes the Kitaev chain (a 1D array) from the Kitaev edge (the 1D edge of a 2D array) [42]. The fact that all two-and four-Majorana terms appear on equal footing, that is, there is no statistical distinction between α 2j −1 ,κ 2j −1 and α 2j ,κ 2j determines that the edge Hamiltonian is exactly self-dual in the sense of quantum statistical mechanics [45].…”
Section: Interacting Kitaev Edgementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this term is what distinguishes the Kitaev chain (a 1D array) from the Kitaev edge (the 1D edge of a 2D array) [42]. The fact that all two-and four-Majorana terms appear on equal footing, that is, there is no statistical distinction between α 2j −1 ,κ 2j −1 and α 2j ,κ 2j determines that the edge Hamiltonian is exactly self-dual in the sense of quantum statistical mechanics [45].…”
Section: Interacting Kitaev Edgementioning
confidence: 99%
“…These zero modes overlap to form a dispersive one-dimensional (1D) edge mode of Majorana fermions [38][39][40]. Backscattering by disorder is not forbidden, yet this "Kitaev edge mode" does not localize [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…[28], where it was shown that with increasing disorder a topological state transits to a metal. The effect of disorder in Kitaev chains has also been studied [29]. Other pertinent studies include, how an onsite disorder can induce [30] a topological phase in a trivial system (which has the necessary ingredients to produce topological phases), and an interesting concept of "statistical topological insulators" which requires another statistical symmetry apart from the symmetry protecting the topological phase [31].…”
Section: Introductionmentioning
confidence: 99%
“…Among the peculiar properties of topologically conserved surface states one can be addressed: i) theoretically proposed by Fu and Kane [4], and experimentally observed [5,6] -wave-like superconducting correlations emerged via proximity coupling 3DTI to a conventional -type superconductor ii) the emergence of chiral Majorana mode [7] at the ferromagnet/superconductor (F/S) interface, which is of experimentally importance to detect the Majorana fermions [8,9]. However, chiral Majorana mode, which corresponds to the zero-energy bound state has a significant impact on the low-energy electron-hole excitations, leading to modifying Andreev reflection (AR) at the F/S interface [10] and thermal transport [11,12]. On the other hand, anisotropic -wave asymmetry pairing due to including nodal points in its superconducting gap can give rise to potentially forming the zero-energy Andreev bound state and, of course, zero-bias conductance [13,14].…”
Section: Introductionmentioning
confidence: 99%